Out-of-field doses in pediatric craniospinal irradiations with 3D-CRT, VMAT, and scanning proton radiotherapy: A phantom study - Majer, Marija; Ambrožová, Iva; Davídková, Marie; De Saint-Hubert, Marijke; Kasabašić, Mladen; Knežević, Željka; Kopeć, Renata; Krzempek, Dawid; Krzempek, Katarzyna; Miljanić, Saveta; Mojżeszek, Natalia; Veršić, Ivan; et al. (Medical physics, 2022)
PURPOSE: Craniospinal irradiation (CSI) has greatly increased survival rates for patients with a diagnosis of medulloblastoma and other primitive neuroectodermal tumors. However, as it includes exposure of a large volume of healthy tissue to unwanted doses, there is a strong concern about the complications of the treatment, especially for the children. To estimate the risk of second cancers and other unwanted effects, out-of-field dose assessment is necessary. The purpose of this study is to evaluate and compare out-of-field doses in pediatric CSI treatment using conventional and advanced photon radiotherapy (RT) and advanced proton therapy. To our knowledge, it is the first such comparison based on in-phantom measurements. Additionally, for out-of-field doses during photon RT in this and other studies, comparisons were made using analytical modeling. METHODS: In order to describe the out-of-field doses absorbed in a pediatric patient during actual clinical treatment, an anthropomorphic phantom, which mimics the 10-year-old child, was used. Photon 3D-conformal RT (3D-CRT) and two advanced, highly conformal techniques: photon volumetric-modulated arc therapy (VMAT) and active pencil beam scanning (PBS) proton RT were used for CSI treatment. Radiophotoluminescent and poly-allyl-diglycol-carbonate nuclear track detectors were used for photon and neutron dosimetry in the phantom, respectively. Out-of-field doses from neutrons were expressed in terms of dose equivalent. A two-Gaussian model was implemented for out-of-field doses during photon RT. RESULTS: The mean VMAT photon doses per target dose to all organs in this study were under 50% of the target dose (i.e., <500 mGy/Gy), while the mean 3D-CRT photon dose to oesophagus, gall bladder, and thyroid, exceeded that value. However, for 3D-CRT, better sparing was achieved for eyes and lungs. The mean PBS photon doses for all organs were up to three orders of magnitude lower compared to VMAT and 3D-CRT and exceeded 10 mGy/Gy only for the oesophagus, intestine, and lungs. The mean neutron dose equivalent during PBS for eight organs of interest (thyroid, breasts, lungs, liver, stomach, gall bladder, bladder, prostate) ranged from 1.2 mSv/Gy for bladder to 23.1 mSv/Gy for breasts. Comparison of out-of-field doses in this and other phantom studies found in the literature showed that a simple and fast two-Gaussian model for out-of-field doses as a function of distance from the field edge can be applied in a CSI using photon RT techniques. CONCLUSIONS: PBS is the most promising technique for out-of-field dose reduction in comparison to photon techniques. Among photon techniques, VMAT is a preferred choice for most of out-of-field organs and especially for the thyroid, while doses for eyes, breasts, and lungs are lower for 3D-CRT. For organs outside the field edge, a simple analytical model can be helpful for clinicians involved in treatment planning using photon RT but also for retrospective data analysis for cancer risk estimates and epidemiology in general.
Keywords: Cerebellar Neoplasms; retrospektivní studie; Humans; Radiotherapy Dosage; kritické orgány; Radiotherapy, Conformal; protony; Protons; celková dávka radioterapie; Craniospinal Irradiation; Radiotherapy Planning, Computer-Assisted; mužské pohlaví; plánování radioterapie pomocí počítače; konformní radioterapie; radioterapie s modulovanou intenzitou; kraniospinální iradiace; lidé; dítě; Child; nádory mozečku; Male; Organs at Risk; Retrospective Studies; Radiotherapy, Intensity-Modulated